Mentoring: concepts, faculty development and erspectives - Pazin-Filho, Antonio; Soriano, Leonardo Araujo; Paula, Jayter Silva de (Medicina (Ribeirao Preto), 2016)
The mentoring approach had its origins related to the learning processes of industrial functions in the 1970’s and was introduced in medical training by the end of 1990’s. Initially, its inclusion in medical schools was incipient and not a part of the formal curriculum or institutional educational guidelines. These facts have prompted several adjustments and led to a gap from its original aims, being often considered as either scientific initiation or emotional supporting activities. This article discusses the problems related to both the mentoring identity and establishment in the medical teaching environment and proposes a concept related to its former sources. We also emphasized the difficulties in assessing the process efficiency and training of tutors, consequent to the lack of patterns to determine the skills expected in this function. Mentoring needs and magnitude in the medical field are also discussed